2014
DOI: 10.1039/c4cc01045k
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of a neutral platinum(ii) complex into highly emitting microcrystalline fibers through metallophilic interactions

Abstract: The solvent-assisted self-assembly of a blue-emitting neutral platinum(II) complex into micrometer-long and highly crystalline fibers has been achieved. The aggregates show highly efficient (quantum yield up to 74%) polarized yellow-orange light emission, as a consequence of their high degree of supramolecular order imparted by weak non-covalent intermolecular (metal···metal and π-π) interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 20 publications
5
88
0
Order By: Relevance
“…In this regard, dianionic tridentate N^N^N ligands bearing pyrazolate [69], triazolate [6973] or tetrazolate [74] units have been used to successfully prepare highly luminescent neutral platinum(II) complexes in dilute solution and/or as aggregated state. Due to their promising emitting features, these complexes have also been employed as phosphors in optoelectronic devices [7172]. Neutral platinum(II) complexes with an asymmetrical triazolate- and tetrazolate-containing tridentate ligand, complexes 28 , were also reported [75] (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…In this regard, dianionic tridentate N^N^N ligands bearing pyrazolate [69], triazolate [6973] or tetrazolate [74] units have been used to successfully prepare highly luminescent neutral platinum(II) complexes in dilute solution and/or as aggregated state. Due to their promising emitting features, these complexes have also been employed as phosphors in optoelectronic devices [7172]. Neutral platinum(II) complexes with an asymmetrical triazolate- and tetrazolate-containing tridentate ligand, complexes 28 , were also reported [75] (Fig.…”
Section: Reviewmentioning
confidence: 99%
“…In this respect, Mauro et al 58 have recently reported a neutral Pt(II) complex which bears CF 3 groups on the triazolyl moieties and an 4-amylpyridine as the ancillary ligand (complex 8 in Chart 1).…”
Section: From Molecules To 3d Architecturesmentioning
confidence: 99%
“…58,59 These derivatives contain dianionic N trz^Npy^Ntrz -based ligands as chromophoric moiety, where trz is a 1,2,4-triazolate moiety and py is a pyridyl group, and an ancillary pyridine which can be functionalized to improve solubility and tune self-assembly properties.…”
Section: From Molecules To 3d Architecturesmentioning
confidence: 99%
“…[2][3][4][5] In addition, d 8 platinum(II) complexes have attracted much attention due to their interesting luminescence properties. [6][7][8][9][10] Cyclometallated derivatives are usefully employed for the preparation of triplet emitters for highly efficient OLED (organic light emitting diode) devices 7,[11][12][13][14] and for their appealing second-order nonlinear optical (NLO) properties. [15][16][17][18] Another fast emerging field regarding luminescent Pt(II) complexes is their application as luminescent labels for bioimaging.…”
Section: Introductionmentioning
confidence: 99%